The use of e-learning in higher education - Маракушин Андрій Ігоревич (Andriy Marakushyn); Чередніченко Артем Вікторович (Artem Cherednichenko) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: analyzing the possibility of introducing means "e-learning" in the sphere of student physical culture and sport. Material and Methods: in the study used theoretical methods, including analysis and synthesis of literature and materials located on the Internet. Results: considered theoretical information about "e-learning". Conclusions: It was found that there are many definitions of the term "e-learning"; established the existence of: common elements of distance and "e-learning"; specific qualitative properties of e-learning, strengths and weaknesses. On the basis of theoretical analysis of "e-learning" can be argued that "e-learning" can and should be embedded in the sphere of student physical culture and sports.